Maslahah and Sakinah Family's Review of Marriage through Marriage Dispensation in Central Lampung Regency - Iim Fahimah; Zaenal Zaenal (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
Some couples are not of legal age who have received a marriage dispensation. A search was conducted on their post-marriage conditions. Whether this early life is subjected to separation or is it precisely harmonious. The authors researched couples who married through the marriage dispensation route in Central Lampung Regency. How do maslahah and sakinah families review the marriage through the marriage dispensation route in Lampung Tengah Regency? Marriage through the marriage dispensation route in central Lampung Regency is in the review of Maslahah and the sakinah family that their marriage is classified as a group of Sakinah II families bringing benefits to their households. In general, the values of the maslahat are obtained in three stages; the benefit obtained at the time of the implementation of the marriage dispensation took place, by obtaining the legality of the couple's conjugal relationship has been valid. The benefit in their home life is due to their good and harmonious relationship, and can be beneficial for those around them. The future benefit of the couple's household and their future child, due to their legal marriage